KARAKTER VEGETATIF DAN GENERATIF BEBERAPA VARIETAS PADI SENSITIF ALUMINIUM - Siti Hartati Yusida Saragih; Eva Sartini Bayu; Mbue Kata Bangun (Universitas Sumatera Utara, 2013)
Vegetative and Generative Characters of Aluminium Sensitive Rice Varieties. Aluminium (Al)tolerant mechanism in rice has not been fully understood. The objective of this research was tostudy the vegetative and generative characters of Al sensitive rice varieties. Five days old of riceseedlings were growned on minimum culture solution containing 15 ppm of Al for 72 hours andthen transferred to non Al-treated culture solution for 48 hours. The selected seedlings wasmeasured based on RRG value. RRG value was determined based on after Al-stress. This researchwas held at Greenhouse in Faculty of Agriculture, University of North Sumatera Utara, Medan,from May until October 2012, using latin square Design with treatment that was rice varieties:Inpari 3, Inpari 4, Inpari 10, Inpari 12 and Inpari 13. Data analysis showed that varieties with Altreatedwere significantly different the vegetative stage, the flower initation, the time of harvestingand the generative stage time. Varieties were not significantly different the plant height, the numberof tillers, the number of productive tiller, the panicle length, the flag leaf length, the number ofpanicle branches, the number of empty grain per panicle, the grain weight per panicle and the 1000grain weight.Keywords : Varieties, Al Sensitive, Root Re-Growth, Vegetative Characters, Generative Characters